Understanding HIV-1 protease autoprocessing for novel therapeutic development. (July 2013) - Huang, Liangqun; Chen, Chaoping
In the infected cell, HIV-1 protease (PR) is initially synthesized as part of the GagPol polyprotein. PR autoprocessing is a virus-specific process by which the PR domain embedded in the precursor catalyzes proteolytic reactions responsible for liberation of free mature PRs, which then recognize and cleave at least ten different peptide sequences in the Gag and GagPol polyproteins. Despite extensive structure and function studies of the mature PRs as well as the successful development of ten US FDA-approved catalytic-site inhibitors, the precursor autoprocessing mechanism remains an intriguing yet-to-be-solved puzzle. This article discusses current understanding of the autoprocessing mechanism, in an effort to prompt the development of novel anti-HIV drugs that selectively target precursor autoprocessing.